Memristor-based crossbar architecture for digital logic implementation/ Mohamad Firdaus Ahmad Patanah - Ahmad Patanah, Mohamad Firdaus (2014)
It has been discovered that, the transistors become an issue where in digital implementation where the dimension of the transistor cannot be shrink any further. Other than that, due to the limitation of materials and current technology have become more relevant as the demanding on the higher density of electronics. In this project, an alternative solution is investigated for the implementation of digital module from memristor-based by using crossbar architecture. This project will compare device performances between memristor crossbar design and conventional CMOS technology. These comparison are in attempt to reduce the area and the limitations with analysis of data. LTSPICE open source platform is used to demonstrate the device model and schematic design. The EDA Tools such as Silvaco Expert is used to design the layouts for conventional CMOS and memristor crossbar design. The dimensions for the memristor layout is based on the published works only. The design implementation that has been carried out are inverting and non-inverting configurations, wired-AND and also for NAND gate with the analysis of data needed. By using memristor-based crossbar architecture, the devices is smaller with a high density and low power consumption.